2015
DOI: 10.3748/wjg.v21.i11.3308
|View full text |Cite
|
Sign up to set email alerts
|

Significant risk and associated factors of active tuberculosis infection in Korean patients with inflammatory bowel disease using anti-TNF agents

Abstract: AIM:To evaluate the incidence and risk factors of Korean tuberculosis (TB) infection in patients with inflammatory bowel disease (IBD) undergoing anti-TNF treatment. METHODS:The data of IBD patients treated with anti-TNFs in 13 tertiary referral hospitals located in the southeastern region of Korea were collected retrospectively. They failed to show response or were intolerant to conventional treatments, including steroids or immunomodulators. Screening measures for latent TB infection (LTBI) and the incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 35 publications
3
37
3
Order By: Relevance
“…Higher proportions of the patients who underwent screening were observed in the sensitivity analyses, but the data still suggest that about a quarter of patients do not undergo TST/IGRA. Although only a few studies have reported the frequency of tuberculosis screening of patients receiving anti‐TNF therapy, the proportion of the patients who had undergone TST/IGRA in the present study (66% in the base‐case analyses and 74–78% in the sensitivity analyses) was substantially lower than the proportions reported in post‐marketing surveillance of ETN (94%) and ADA (89%) prescribed for rheumatoid arthritis patients in Japan, and also lower than that in a hospital‐based study of inflammatory bowel disease in Korea (82%) . The proportion was even lower for the screening combined with chest radiography.…”
Section: Discussioncontrasting
confidence: 80%
“…Higher proportions of the patients who underwent screening were observed in the sensitivity analyses, but the data still suggest that about a quarter of patients do not undergo TST/IGRA. Although only a few studies have reported the frequency of tuberculosis screening of patients receiving anti‐TNF therapy, the proportion of the patients who had undergone TST/IGRA in the present study (66% in the base‐case analyses and 74–78% in the sensitivity analyses) was substantially lower than the proportions reported in post‐marketing surveillance of ETN (94%) and ADA (89%) prescribed for rheumatoid arthritis patients in Japan, and also lower than that in a hospital‐based study of inflammatory bowel disease in Korea (82%) . The proportion was even lower for the screening combined with chest radiography.…”
Section: Discussioncontrasting
confidence: 80%
“…Our rate for presumed LTBI (4%) was also lower than in a Korean cohort of anti-TNF treated patients 11. These differences probably reflect our strategy of active identification of LTBI through screening, and different background TB incidence rates.…”
Section: Discussioncontrasting
confidence: 68%
“…The interferon gamma release assay is also not widely available in local public hospitals. In a recent Korean study 4.2% of patients were reported to develop active tuberculosis infection after using anti‐TNF agents . Hence, it is mandatory to have adequate screening of these patients prior to the initiation of anti‐TNF therapy in Asia.…”
Section: Discussionmentioning
confidence: 99%